Senza domani - Trione, Aldo (Bollettino Filosofico, 2015)
Nikolas Lenau’s lines, at the beginning of Max Horkheimer’s Dawn and Decline, represents an unprejudiced reflection on how art and the arts are declining in the twentieth century’s intellectual civilization. The paper deals with Cioran’s philosophy of the absurd and the idea of “extreme” desperation, and the surreal fable of Hofmannstal’s Lord Chandos. The essay proposes a parva clavis useful to investigate the indissoluble bond between contemporary poetry and the “decline of ontology”.